2020
DOI: 10.1136/bmjopen-2020-038375
|View full text |Cite
|
Sign up to set email alerts
|

Gap between real-world data and clinical research within hospitals in China: a qualitative study

Abstract: ObjectiveTo investigate the gap between real-world data and clinical research initiated by doctors in China, explore the potential reasons for this gap and collect different stakeholders’ suggestions.DesignThis qualitative study involved three types of hospital personnel based on three interview outlines. The data analysis was performed using the constructivist grounded theory analysis process.SettingSix tertiary hospitals (three general hospitals and three specialised hospitals) in Beijing, China, were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The challenge of applying EMR data to clinical research in China is the lack of data interoperability and the difficulty of extracting free text data. The main highlight is the concern that hospital management departments have regarding the data security [ 11 ]. The purpose of clinical research is to solve clinical practice problems, and strengthening the hospital clinical research source data management is the foundation for improving the quality of the clinical research data in China.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of applying EMR data to clinical research in China is the lack of data interoperability and the difficulty of extracting free text data. The main highlight is the concern that hospital management departments have regarding the data security [ 11 ]. The purpose of clinical research is to solve clinical practice problems, and strengthening the hospital clinical research source data management is the foundation for improving the quality of the clinical research data in China.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NUWA platform promotes the integration of medical data in China. At present, patients' inpatient and outpatient information and genetic data are generally stored in different hospitals, making it challenging to understand the patient's entire diagnosis and treatment process 20,21 . Therefore, data fragmentation and information silos grow because of the independence and isolation of real‐world data sources from one another, various data management systems, decentralised data storage and diverse data standards, and difficulties in horizontal data integration and exchange 22 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, patients' inpatient and outpatient information and genetic data are generally stored in different hospitals, making it challenging to understand the patient's entire diagnosis and treatment process. 20,21 Therefore, data fragmentation and information silos grow because of the independence and isolation of real-world data sources from one another, various data management systems, decentralised data storage and diverse data standards, and difficulties in horizontal data integration and exchange. 22 The NUWA platform uses a self-developed GO-specific data curation pipeline to normalise the data from EMRs and fully integrates patient information across various systems.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…[15][16][17][18] The first qualitative study on the problem of the gap between RWD and clinical research found several key problems, which included the lack of data standards usage, prevalence of unstructured data and data security concerns. 19 Similarly, a literature review in China revealed that meaningful usage of RWD for clinical research is deterred by weak regulatory implementation of semantic level data standards, prevalence of unstructured data, and difficult hospital data access. 20 It is urgently important to address the standardisation of RWD for clinical research in China.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The data standards in China were developed by the Statistical Information Centre of the National Health Commission and used to evaluate the interoperability of hospital information systems 15–18. The first qualitative study on the problem of the gap between RWD and clinical research found several key problems, which included the lack of data standards usage, prevalence of unstructured data and data security concerns 19. Similarly, a literature review in China revealed that meaningful usage of RWD for clinical research is deterred by weak regulatory implementation of semantic level data standards, prevalence of unstructured data, and difficult hospital data access 20.…”
Section: Introductionmentioning
confidence: 99%